IMPLEMENTASI KURIKULUM MERDEKA DI MAN BANTAENG KABUPATEN BANTAENG - Afdil Hidayatul Habib; Abdul Hakim; Arnidah (STKIP Subang, 2026)
This study analyzes the implementation of the Merdeka curriculum at MAN Bantaeng. This study aims to describe the implementation of the Merdeka curriculum, the implementation of the Pancasila Student Profile Strengthening Project (P5), and obstacles in implementing the Pancasila Student Profile Strengthening Project. The research approach used is qualitative with a descriptive research type that aims to determine the implementation of the Merdeka curriculum. This research was conducted at MAN Bantaeng, in the even semester of the 2023/2024 academic year. The data sources for this study were the principal, teachers, and students who determined the research subjects themselves through criteria determined by the researcher, namely being willing to conduct interviews, teachers in charge of the curriculum, and students at MAN Bantaeng. Data collection techniques used were observation, interviews, documentation, and literature studies. The data analysis methods used consisted of data collection, data reduction, data presentation, and drawing conclusions. Based on the results of research through the process of observation and interviews with subject teachers, curriculum teachers and students on June 10, 2024, the implementation of the independent curriculum at MAN Bantaeng began in 2022 and then became the first madrasah school to implement the independent curriculum in Bantaeng district. In its implementation in the first year it did not run optimally due to the need for continuous adaptation, however, as the implementation and learning process progressed, teachers continued to provide understanding to students regarding the independent curriculum. Based on the results of interviews with the Principal of Madrasah, Deputy Head of Curriculum, Subject Teachers and students of MAN Bantaeng, the Implementation of the Pancasila Student Profile Strengthening Project (P5) has been carried out in accordance with the themes and characteristics of learning by MAN Bantaeng by raising several themes.